Controle da esquistossomose: atividade moluscicida e cercaricida do óleo essencial de Citrus x limon (L.) Osbeck - CARVALHO, Amália Cristina Melo (2018)
"Control of schistosomiasis: molluscicidal and cercaricidal activity of Citrus x limon (L.) Osbeck essential oil". Schistosomiasis is a disease still considered a serious public health problem in Brazil, its occurrence is closely associated with a lack of socioenvironmental conditions and is endemic in several Brazilian states, including Maranhão. Schistosoma mansoni, a parasite that transmits the disease, requires the snail of the genus Biomphalaria to complete its life cycle, which is the intermediate host. Thus, one of the forms of disease control is the interruption of the biological cycle of helminth by means of the combat of the intermediate host. The objective of this study was to evaluate the molluscicidal and cercaricidal activity of the essential oil of the aerial parts and the fruit epicarp of Citrus x limon (L.) Osbeck, as well as to analyze its chemical composition and toxic action to non - target organisms, aiming to find a viable and management of schistosomiasis. The essential oils under study were extracted by the hydrodistillation technique and the chemical composition was determined by gas chromatography coupled to mass spectrometry. The molluscicidal and cercaricidal activity of the oils were evaluated in four concentrations against Biomphalaria glabrata and cercariae of Schistosoma mansoni. Toxicity against non-target organisms was assessed against Artemia saline. The results were expressed as lethal concentrations of biological activities, with 95% confidence level, obtained by linear regression. Only the oil extracted from the epicarp of the fruit showed activity against Biomphalaria glabrata with CL90 90.08μg / mL. Oils extracted from the aerial parts and the epicarp exhibited cerivastatic activity of Schistosoma mansoni with CL50 values 1.33 and 1.05 μg / mL, respectively. The evaluated essential oils presented moderate toxicity to the microcracks Artemia salina. This result leads us to conclude that the species studied has great potential to be used as a viable and sustainable bioactive alternative such as molluscicide and cercaricide. The challenge is to generate new data that help to control neglected diseases, an area that still requires investments and research with a satisfactory return.